EVALUATION ON NEEM BASED FORMULATIONS VIS-À-VIS DICHLORVOS AGAINST MECONELLICOCCUS HIRSUTUS - SRINIVAS, T.; PRASAD, K. SATHYA; SHEKHAR, M. A.; MANJUNATH, D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
Four neem products viz. neem kernel extract, neem oil cake extract, neem oil and one commercial neem formulation (Rakshak) were tested against the mealy bug, Maconellicoccus hirsutus. Though the pest is known to attack mulberry since 1919, it has assumed the key pest status, especially in Karnataka, Andhra Pradesh and Tamil Nadu since only about a decade. The infestation by mealy bug causes the apical shoot malformation, popularly known as Tukra resulting in considerable qualitative and quantitative damage to the mulberry. The average incidence of Tukra in mulberry is reported to be 34.24% leading to an estimated leaf yield loss of about 4500 kgs has yr. In mulberry crop Systems, an IPM package comprising mechanical, chemical (spraying of 0.2% DDVP in 0.5% soap Solution) and biological strategies has been developed for the management of the pest in question. In recent years the bioactive products of plant origin, especially the neem products have been recognized as invaluable in pest control strategies. Hence an attempt is made to screen neem products against the mealy bug. The result demonstrates that the neem kernel extract and the commercial neem extract based products Rakshak have induced mild ovicidal action and appreciable nymphal and adult mortality of M. hirsutus, which is comparable to the effect of dichlorvos. The results are discussed in the light of utilizing the neem products as an alternative to chemical insecticide can be replaced with any of the tested neem products for the control of mealy bug.